FEMINITAS, EKOFEMINISME, DAN CERPEN INDONESIA [Femininities, Ecofeminism, and Indonesia Short Story] - Anas Ahmadi (TOTOBUANG, 2017)
Research about femininity in literature is not a new thing. However, studies of femininitythat related with environmental philosophy and ecofeminism in literature are still warmly discussed. During this time, the environmental movement has mostly dominated by men. However, along with the emergence of ecofeminism, women also want to be involved in the environmental movement. Ecofeminists want to save the environment by their own way. Therefore,this study described about femininity which has  relation with the environment. This study used descriptive-interpretative approach, while the data source used  Cerpen Kompas 2012-2015. It had appeared in the 2012-2015 Compass Short Story Collection. The emergence of the femininity appeared through the following segments. First, women who love plants weredisplaying through figure’thoughts and actions  in loving plants. Second, women and environmental management weredisplaying through female’s figure who were able to makethe clean environment. Third, women who longed thenature wererepresented by female’ figurewho yeared surroundingnature, rain and river. Futhermore,inthe short stories that written in compass collection, it seems that there were still few authors who raised women in the frame of ecofeminism. Whereasecofeminismthat appears in the literature is one author’s way to save the environment. Penelitian tentang feminitas dalam sastra memang bukanlah hal yang baru. Namun, penelitian feminitas yang dikaitkan dengan filsafat lingkungan dan ekofeminisme dalam sastra masih hangat diperbincangkan. Selama ini, gerakan lingkungan lebih banyak didominasi oleh kaum laki-laki. Namun, seiring dengan munculnya ekofeminism, perempuan juga ingin berkecimpung dalam gerakan lingkungan. Para ekofeminis ingin menyelamatkan lingkungan dengan cara mereka. Berkait dengan hal tersebut, dalam penelitian ini dipaparkan tentang feminitas dalam kaitannya dengan lingkungan. Penelitian ini menggunakan pendekatan deskriptif-interpretatif, sedangkan sumber data yang digunakan adalah Cerpen Kumpulan Kompas tahun 2012—2015. Hal tersebut muncul dalam Kumpulan Cerpen Pilihan Kompas 2012—2015. Pemunculan feminitas tersebut tampak melalui segmen berikut. Pertama, perempuan yang mencintai tumbuhan, ditampilkan melalui pemikiran dan tindakan tokoh dalam mencintai tumbuhan. Kedua, perempuan dan pengelolaan lingkungan, ditampilkan melalui tokoh perempuan yang mampu membuat lingkungan menjadi bersih. Ketiga, perempuan yang merindu alam, ditampilkan melalui tokoh perempuan yang merindu alam sekitar, hujan dan sungai. Berkait dengan pemunculan ekofeminisme dalam sastra Indonesia, lebih spesifik kumpulan cerpen Kompas tampaknya masih sedikit pengarang yang mengangkat perempuan dalam bingkai ekofeminisme. Padahal, ekofeminisme yang muncul dalam sastra merupakan salah satu bentuk suara pengarang untuk menyelamatkan lingkungan.